The 9th International Symposium on Rock Fragmentation by Blasting, Fragblast 9, 14-17th of September 2009, Granada, Spain - Agne Rustan (International Society of Explosives Engineers, 2009)
The 9th International Symposium on Rock Fragmentation by Blasting was held in the Granada Conference Centre, Granada, Spain from the 14th - 17th September 2009. The Symposium was preceded by a 1 ½ day Workshop on “Vibrations from Blasting” organized by the initiator Dr. Alex Spathis and his colleague M. J. Noy, both employed at Orica Mining, Australia. Prof. Josè Sanchidrian at the “Universidad Politécnic de Madrid” in Madrid, Spain was the main organizer for both the Workshop and the Symposium. A record number of participants came (292) from a record number of countries (41). There were a total of 14 papers in the Vibrations from Blasting Seminar and 96 papers and 2 Keynote Addresses in the Fragblast 9 Symposium itself. The aim with this paper is to present some results from Fragblast 9 which are of interest for a large target group. One very important result from the Fragblast 9 meeting was that it was decided there that Fragblast 10 will be held in November 2012 New Delhi India.